2021
DOI: 10.1097/md.0000000000026500
|View full text |Cite
|
Sign up to set email alerts
|

Classification of circadian pain rhythms and pain characteristics in chronic pain patients

Abstract: This study aimed to perform cluster analysis in patients with chronic pain to extract groups with similar circadian rhythms and compare neuropathic pain and psychological factors among these groups to identify differences in pain-related outcomes. A total of 63 community-dwellers with pain lasting at least 3 months and Numerical Rating Scale scores of ≥2 were recruited from 3 medical institutions. Their pain circadian rhythms were evaluated over 7 days by measuring pain intensity at 6-time points per day using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Patients were asked to report if they felt any abnormal sensation of burning, cold, or stinging at the site of cream application and were followed up at 0, 2, and 6 hours for the same. The study was conducted between 9 AM and 11 AM to minimize the influence of circadian difference on pain sensitivity [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients were asked to report if they felt any abnormal sensation of burning, cold, or stinging at the site of cream application and were followed up at 0, 2, and 6 hours for the same. The study was conducted between 9 AM and 11 AM to minimize the influence of circadian difference on pain sensitivity [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Variations in peak pain intensity have also been observed in headache conditions ( Burish et al, 2019 ). Other work examining a population of patients with heterogeneous chronic pain reported three differing active phase pain rhythms in separate clusters of patients ( Tanaka et al, 2021 ). Finally, another study observed pain rhythms in patients with diabetic peripheral neuropathy or postherpetic neuralgia.…”
Section: Circadian Rhythms Of Pain Behavior and Pain Sensitivitymentioning
confidence: 99%
“…All sessions were conducted in the same clinical setting, in a quiet room with ambient light, temperature, and humidity-controlled between 23ºC-24ºC and 30%-35%, respectively. Participants were assessed at approximately the same time of the day to increase repeatable testing conditions between days [22]. Prior to running the psychophysical tests, participants completed a battery of questionnaires on sleep disturbances with the Medical www.epain.org…”
Section: Participants and Proceduresmentioning
confidence: 99%